Development of Multicultural-Based Nahwu Teaching Materials to Strengthen Religious Moderation at Islamic Higher Education Institutions in Indonesia - Anggara, Syamfa Agny; Nashoih, Afif Kholisun (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study was motivated by the need to develop multicultural-based nahwu teaching materials to address challenges in understanding Arabic grammatical concepts within an inclusive and contextually relevant framework aligned with the values of religious moderation. The research aimed to produce nahwu materials that not only introduce grammatical concepts but also internalize multicultural and moderation values throughout the learning process. This study employed a Research and Development (R&D) approach, adapting the Borg and Gall development model. Data were collected through observation, questionnaires, and tests, involving two expert validators. The development results show that the teaching materials present nahwu content systematically, integrating examples that reflect Indonesia’s cultural diversity. Expert evaluations indicate that the materials are highly suitable for use, with a validity score of 81.11%. Field trial results also demonstrate a significant improvement in student learning outcomes, with pretest and posttest averages of 60.33 and 81.17, respectively, signifying an increase of 20.84 points. Therefore, the multicultural-based nahwu textbook is effective in enhancing students’ understanding of nahwu concepts while fostering religious moderation values in Arabic language learning. This finding is further supported by positive student responses, which achieved a score of 81.11%, categorized as “excellent” in terms of eligibility criteria.